2017
DOI: 10.1111/pde.13098
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Targeted High‐Intensity Medium‐Band (304–312 nm) Ultraviolet B Light in Pediatric Vitiligo

Abstract: Targeted high-intensity medium-band UVB phototherapy alone can produce clinical improvement in pediatric vitiligo and is well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…22 This study suggested that combination treatment may be more effective than NB-UVB monotherapy, but the study was small and so lacked power to demonstrate any statistically significant difference between the intervention groups; the relative risk ratio for achieving > 75% repigmentation was 1.38 (95% CI 0.71 to 2.68). 83 No significant safety issues have been identified in previous small studies of home-based hand-held phototherapy devices for vitiligo, used instead of hospital NB-UVB therapy, 25,26 and this is confirmed by the findings of our study. Long-term NB-UVB treatment (mean number of treatments = 211) in a study of patients with darker skin types conferred no increase in skin cancer risk, suggesting that NB-UVB can safely be continued for longer periods of time than in our study, although most patients in that study were skin types IV-VI.…”
Section: Relevance To the Wider Literaturesupporting
confidence: 84%
See 3 more Smart Citations
“…22 This study suggested that combination treatment may be more effective than NB-UVB monotherapy, but the study was small and so lacked power to demonstrate any statistically significant difference between the intervention groups; the relative risk ratio for achieving > 75% repigmentation was 1.38 (95% CI 0.71 to 2.68). 83 No significant safety issues have been identified in previous small studies of home-based hand-held phototherapy devices for vitiligo, used instead of hospital NB-UVB therapy, 25,26 and this is confirmed by the findings of our study. Long-term NB-UVB treatment (mean number of treatments = 211) in a study of patients with darker skin types conferred no increase in skin cancer risk, suggesting that NB-UVB can safely be continued for longer periods of time than in our study, although most patients in that study were skin types IV-VI.…”
Section: Relevance To the Wider Literaturesupporting
confidence: 84%
“…This is consistent with previous research, which has shown that combination treatments are generally more effective than monotherapies in treating vitiligo, although overall response rates, both in our study and in previous research, are generally modest. 22,25,26 Although there have not been any studies assessing the same interventions as those used in this study, the response rates are comparable with other studies. A meta-analysis of studies assessing phototherapy for vitiligo, 82 including 29 prospective studies of NB-UVB, reported a 'marked response' (> 75% repigmentation) in around 19% of participants after 6 months of NB-UVB monotherapy.…”
Section: Relevance To the Wider Literaturesupporting
confidence: 76%
See 2 more Smart Citations
“…NB‐UVB is usually reserved for people with extensive vitiligo and is delivered in secondary care using full‐body units, requiring regular hospital attendance 22 . Limited vitiligo can be treated with handheld NB‐UVB devices, 25 but studies assessing these have been retrospective, or too small to inform clinical practice 26,27 . Using a handheld NB‐UVB device reduces the need for hospital visits and avoids exposure of unaffected skin to NB‐UVB.…”
mentioning
confidence: 99%